Investigation of the Protective Role of Carotene Against Toxicity Encouraged by Ammonium Sulfate in Albino Mice - Emine Yalçın; Ali Acar; Kültiğin Çavuşoğlu (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2017)
The aim of this study is to investigate the genotoxic effects of ammonium sulphate and the protective role of βcarotene against genotoxicity in Swiss albino mice. Albino mice divided into one control group and five treatment groups. The body weight gain, MN frequency in erythrocyte and buccal mucosa epithelial cell, frequency of chromosomal abnormalities were investigated as genotoxicity parameters. It is determined that ammonium sulphate treatment was caused a statistically decrease in body weight gain and increase in frequency of MN and chromosomal abnormalities according to control group. It was determined that β-carotene treatment was improved the genotoxicity induced from ammonium sulphate, and caused an increase in body weight gain and a decrease in frequencies of MN and of chromosomal abnormalities. As a result, β-carotene treatment can be used in reduction of toxicity caused by chemicals as a toxicity restricting agent in near future.